First- and second-order electrical properties computed at the FSMRCCSD level for excited states of closed-shell molecules using the constrained-variational approach - Bag, Arijit; Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2009)
Fock space multireference coupled-cluster (FSMRCC) method emerged as an efficient tool to describe the electronic structure of nearly degenerate cases. Development of linear response has been one of the challenging problems in FSMRCC due to the multiple-root nature of the effective Hamiltonian. A response from any of the roots would span the space for getting the properties. Hence, all roots perturbed by the external field would proliferate the excited states. We recently developed the FSMRCC method for the efficient evaluation of analytic response properties using a constrained variation approach. In this paper, we present analytic dipole moments and polarizabilities of H2O, O-3, and CH+ molecules in low-lying excited states along with brief discussion of singlet triplet decoupling of (1,1) sector of FSMRCC resulting from spin adaptation. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3167796]

Fock-space multi-reference coupled-cluster response with the effect of triples on dipole moment of ClO and SF radicals - Ravichandran, Lalitha; Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2012)

Fock space multireference coupled cluster theory: study of shape resonance - Bhattacharya, Sumantra; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2013)
The complex absorbing potential along with correlated independent particle potential (CIP) Fock space multireference coupled cluster method is used for the study of resonances. We have studied shape resonance of e(-) - F-2, e(-) - N2O and e(-) -CO molecules. In particular, we have studied e(-) - F-2 scattering at different bond lengths to know whether F-2(-) is bound at the equilibrium bond length of F-2. (C) 2013 Wiley Periodicals, Inc.
Keywords: correlated independent particle potential; Fock-space multireference coupled cluster theory; shape resonance